Research on Energy Saving Algorithm of 5G Relay Cellular Network - Yangbo Guo; Zhizhong Zhang; Haonan Hu; Fang Cheng (Dianxin kexue)
The energy saving issue of 5G relay cellular network was discussed.Relay technology is an important technology in the fifth generation mobile communication network（5G）.By switching some base stations with low traffic into sleep mode,the energy can be saved.Therefore,the state of base stations in 5G may convert usually,the network topology and business changed over time.Considering both quality of service（QoS）and power consumption of the whole network,a dynamic energy saving（DES）algorithm was proposed to optimize the overall performance of QoS and energy efficiency for 5G relay cellular network.Simulation results under different traffic conditions demonstrate that the DES algorithm can reconfigure the network,shut down part of the base station and relay nodes to significantly reduce energy consumption,especially when the network load is low.